Analisis Penghematan Daya Listrik dengan Implementasi FX-80 Supervisor Controller pada Sistem Water Chiller - Yoshua, Axel; Wahab, Wahidin; Hugeng (Fakultas Teknologi Informasi, 2024)
This research aims to analyze electrical power consumption and cooling system efficiency between the FX-80 Supervisor Controller and a system without a controller in the field. Measurements are carried out for one year by taking data on electrical power consumption and Coefficient of Performance (COP) every month. The research results show that the system with the FX-80 Supervisor Controller consumes lower electrical power and has a higher COP than the system without the controller. The higher efficiency of systems with controllers represents significant energy savings potential for companies. This research recommends the use of controllers in cooling systems to increase energy efficiency.